Ambient temperature and nest temperature variation in enclosed nests (Spanish sparrow) and open-cup nests (Iberian azurewinged magpie) - Marques, Paulo A.M. (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
Temperature plays a central role in the life of birds, especially during egg incubation and nestling thermal brooding. I investigated nest temperature variation relative to ambient temperature during incubation in an enclosed nest-builder species (Spanish sparrow "Passer hispaniolensis") and an open-cup nest-builder species (Iberian azurewinged magpie "Cyanopica Cooki").
Keywords: nest temperature; Passerines; Mediterranean climate; adaptation; temperature buffer